Digitally enabled supply chain as a strategic asset for the COVID-19 response in Alberta. Issue 2 (March 2022) - Snowdon, Anne; Wright, Alexandra
This provincial case study, one of seven conducted as part of a national research program on healthcare supply chain management during COVID-19, focuses on Alberta. With a history of emergency preparedness, Alberta's unique context, one that includes having an already established, centralized, and digital healthcare supply chain strategy, sets this case apart from the others in terms of pandemic responses. A key challenge navigated by Alberta was the inadequacies of traditional sourcing and procurement approaches to meet surges in product demand, which was overcome by the implementation of unique procurement strategies. Opportunities for Alberta included the integration of supply chain teams into senior leadership structures, which enabled access to data to inform public health decision-making. This case demonstrated how Alberta's healthcare supply chain assets—its supply chain infrastructure, data, and leadership expertise, especially—contributed to resilient supply chain capacity across the province.